(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Monitoring of treatment parameters is of utmost importance in current medicine. The use of intraocular media and irrigation fluid temperature monitoring during vitreoretinal surgery is, however, not common in current clinical practice. Purpose: To investigate intraocular temperature changes at various time points of vitreoretinal surgery. Materials and Methods: Twenty patients (20 eyes) who underwent vitrectomy with room-temperature (24.2±0.52 ˚С) irrigation solutions at an ambient temperature of 24.4±0.51 °С were under observation. Temperatures in the anterior, mid- and posterior vitreous were recorded before and immediately after vitrectomy and after performance of additional surgical manipulations. Results: The presence of a transvitreous temperature gradient from the anterior toward the posterior vitreous of the human eye was confirmed. At baseline, the highest temperature (34.17±0.36 °С) was recorded in the posterior vitreous. There were significant decreases in temperatures in vitreous compartments immediately after vitrectomy, with the lowest temperature of 30.1±0.45 °С recorded in the anterior vitreous, and the greatest temperature decrease (3.8±0.59 ˚С) compared to baseline, in the preretinal posterior vitreous. There were increases in temperatures in vitreous compartments after additional surgical manipulations and, with an increase in the duration of these manipulations, temperature in the vitreous increased at an average rate of 0.18°C per minute. Conclusion: Vitreoretinal surgery is commonly performed under conditions of artificially induced local hypothermia, warranting intraoperative monitoring of intraocular and irrigation fluid temperatures.